Ahmet B. Ercilasun, Kutadgu Bilig Grameri-Fiil, Basin Yayin Yüksekokul Basimevi. Gazi Universitesi Yayin No. 33, Ankara, pp. XII, 196, 1984. - Frankle Hecht, Eleanor (Estudios de Asia y África, 1989)
-